The Application of Indonesian Language Learning through Communicative Approach at Grade V Students SDN 01 Ulak Karang Selatan Kota Padang - Gusni Aflucya; Nofriza Efendi; Ayunis Ayunis; Stavinibelia Stavinibelia (The Future of Education Journal, 2024)
This research aims to explain and describe the implementation of Indonesian Language Learning through a Communicative Approach in Class V Students of SDN 01 Ulak Karang Selatan, Padang City. This research is motivated by the fact that the use of learning methods in learning Indonesian has not been varied. Therefore, this research aims to describe the teacher's efforts in implementing Indonesian Language learning for Class V Students at SDN 01 Ulak Karang Selatan, Padang City, factors that influence the success of Indonesian Language learning for Class V Students at SDN 01 Ulak Karang Selatan, Padang City. This research uses a qualitative approach with a descriptive type. Then the data was collected through interviews, observation and documentation, then data analysis was carried out through three stages, namely data reduction, data presentation and drawing conclusions. The subjects of this research are class V teachers and students. Based on the research results, it was found that (1) the teacher's efforts in implementing Indonesian language learning for Class V students at SDN 01 Ulak Karang Selatan, Padang City, namely that the teacher still uses the lecture method, where this method is a way of learning or teaching that emphasizes one-way notification from the teacher to the students. (active teacher, passive learner). (2) factors that influence the success of learning Indonesian for Class V Students at SDN 01 Ulak Karang Selatan, Padang City consist of Indonesian Language Learning Competency Standard Factors, Teacher Factors, Student Factors, Family Environment Factors, Facilities and Infrastructure Factors.